1980
DOI: 10.1111/j.1471-4159.1980.tb03705.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Presence of CDP‐Ethanolamine: 1,2‐diacyl‐sn‐glycerol Ethanolaminephosphotransferase in Rat Central Nervous System Myelin

Abstract: Highly purified rat brain myelin isolated by two different procedures showed appreciable activity for CDP-ethanolamine: 1,2-diacyl-sn-glycerol ethanolaminephosphotransferase (EC 2.7.8.1). Specific activity was close to that of total homogenate and approximately 12-16% that of brain microsomes. Three other lipid-synthesizing enzymes, cerebroside sulfotransferase, lactosylceramide sialyltransferase, and serine phospholipid exchange enzyme, were found to have less than 0.5% the specific activity in myelin compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

1982
1982
1989
1989

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…Myelin obtained by the modified Norton and Poduslo (1973) procedure, shown previously to possess very high purity (Wu and Ledeen, 1980;Haley et al, 1981), was found to possess phosphoethanolamine cytidylyltransferase, of specific activity amounting to some 27-32% of that observed in simultaneously isolated microsomes. The same myelin preparations contained virtually negligible levels of t h e microsomal marker NADPH-cytochrome c reductase or the cytosol marker lactate dehydrogenase (Table 1).…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…Myelin obtained by the modified Norton and Poduslo (1973) procedure, shown previously to possess very high purity (Wu and Ledeen, 1980;Haley et al, 1981), was found to possess phosphoethanolamine cytidylyltransferase, of specific activity amounting to some 27-32% of that observed in simultaneously isolated microsomes. The same myelin preparations contained virtually negligible levels of t h e microsomal marker NADPH-cytochrome c reductase or the cytosol marker lactate dehydrogenase (Table 1).…”
Section: Resultsmentioning
confidence: 80%
“…Recent evidence has indicated that the myelin membrane itself has a capacity for synthesis of specific membrane constituents-principally lipids-although such synthesis is not neces-sarily functionally related to the above-mentioned process of myelinogenesis. Evidence for such myelin-localized synthesis came indirectly from experiments demonstrating incorporation of axonally derived substrates into a variety of myelin lipids Ledeen, 1978, 1979;Dtoz et al, 1978Dtoz et al, , 1981Brunetti et al, 1981;Ledeen and Haley, 1983) and more directly from reports of specific lipid-synthesizing enzymes in purified myelin (Costantino-Ceccarini and Suzuki, 1975;Deshmukh et al, 1978;Choi and Suzuki, 1978;Ledeen and Wu, 1979;Wu and Ledeen, 1980;Kunishita and Ledeen, 1982).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our results indicate that CDP-choline : 1,2-diglyceride choline phosphotransferase, Na+ ,K+-ATPase, and 5'-nucleotidase may be myelin-associated, since they all demonstrate RSAs greater than 1.0 in the region of the sucrose gradient (fractions 7-lo), where the paranodal loop regions of myelin may be found. Several laboratories have reported that 5'-nucleotidase (Cammer et al, 1980), Na+,K+-ATPase (Reiss et al, 1981), and CDP-choline : 1 ,Zdiglyceride choline phosphotransferase ( Wu and Ledeen, 1980) are intrinsic CNS myelin constituents. 5'-Nucleotidase has been localized to the outer regions of the myelin sheath (Scott, 1965), but our results indicate that even the least dense multilamellar myelin-rich region of the density gradient has significant 5'-nucleotidase activity (RSA = 1.1).…”
Section: Discussionmentioning
confidence: 99%
“…After thorough mixing by vortexing, the upper phase was clarified by centrifugation (1000 x g for 5 min), and a 1-ml aliquot was counted in 10 ml of Aquasol (Beckman Instruments, Fullerton, CA) in an Intertechnique SL-30 scintillation counter. CDPcholine: 1,2-diglyceride choline phosphotransferase was assayed using the incubation system described by Wu and Ledeen (1980). The radioactive product was extracted by the procedure of Hajra and Radin (1978), and a 0.5-ml aliquot of the radioactive product was evaporated dry and then counted in 5 ml of Aquasol by liquid scintillation counting.…”
Section: Enzymatic Assaysmentioning
confidence: 99%